The influence of post-resuscitation debriefing and clinical learning environment on CPR quality and resuscitation self-efficacy among emergency department healthcare workers - Marintas Marintas; Prima Dewi Dewi; Nurdina Nurdina; Nurwijayanti Nurwijayanti; Yuly Peristiowati (Politeknik Negeri Subang, 2026)
Background: CPR quality and resuscitation self-efficacy are critical for successful cardiac arrest management. Structured debriefing and supportive learning environments are hypothesized to enhance these outcomes. Purpose: This study aimed to evaluate the associations between post-resuscitation debriefing and the clinical learning environment with CPR quality and resuscitation self-efficacy. Methods: A quasi-experimental study with a one-group pretest-posttest design was conducted at the Emergency Department of Undata Hospital. All eligible healthcare workers (n = 51) were recruited using total sampling. Data on post-resuscitation debriefing, clinical learning environment, CPR quality, and resuscitation self-efficacy were collected using validated questionnaires and observation sheets. Bivariate analysis was performed using Spearman's rank correlation test. Multiple linear regression analysis was conducted to identify predictors of CPR quality and resuscitation self-efficacy, controlling for age, work experience, and profession. Statistical significance was set at p < 0.05. Results: Post-resuscitation debriefing was significantly associated with CPR quality (rho = 0.412, p = 0.003) and resuscitation self-efficacy (rho = 0.523, p < 0.001). The clinical learning environment was also significantly associated with CPR quality (rho = 0.456, p = 0.001) and resuscitation self-efficacy (rho = 0.389, p = 0.005). Multiple linear regression analysis identified post-resuscitation debriefing as the strongest predictor of CPR quality (beta = 0.398, p = 0.002) and resuscitation self-efficacy (beta = 0.467, p < 0.001), after controlling for confounding variables. Conclusion: Structured post-resuscitation debriefing and a positive clinical learning environment are significantly associated with improved technical skills and professional confidence among healthcare workers. Implementing standardized debriefing may be an effective strategy for enhancing resuscitation performance in emergency settings.